Pediatric scald injury and its comparison in urban and rural population: a clinico-epidemiological study in a high volume burn centre of Northern India - Srivastava, Sunil; Vij, Vikesh (International Journal Of Community Medicine And Public Health, 2020)
Background: Scalds are the leading cause of pediatric burn admissions and related morbidity, as well as a major cause of pediatric death worldwide. This study was conducted with the objective to study the epidemiological characteristics of pediatric scald injuries and its presentation in urban and rural parts of Indian population. Methods: A retrospective study was conducted by reviewing the medical records of all burn admissions in our institute from January 2017 to December 2019. Data of pediatric patients with scald injury was analyzed. Results: Total 1257 pediatric burn patients were admitted during the study period of which 711 (56.56%) were scald injuries. 57.94% of the children belonged to rural background. The mean Total Burn Surface Area was 38.55% in rural population as compared to 24.16% in the urban population. Immersion burn was most common mode of scald injury in children from rural background (60.19%). Spillage was commonest mode of scald in children from urban background (69.2%) and also the commonest mode of scalds in the pediatric population. Conclusions: The population of rural area had greater total burn surface area, belonged to lower socio-economic status, and had delayed presentation to the hospital and greater mortality rates. Illiteracy and beliefs in quackery further worsened the prognosis of such children.